2002
DOI: 10.1148/radiol.2243011553
|View full text |Cite
|
Sign up to set email alerts
|

Patients with a History of Elevated Prostate-Specific Antigen Levels and Negative Transrectal US–guided Quadrant or Sextant Biopsy Results: Value of MR Imaging

Abstract: In this patient population, MR imaging has higher sensitivity for detection of prostate cancer than DRE or transrectal US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1
17

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(99 citation statements)
references
References 25 publications
2
79
1
17
Order By: Relevance
“…Comet-Battle et al 25 had similar results, with a sensitivity of 80% and specificity of 76% using sextant PB for correlation. Beyersdorff et al 26 exhibited that T2-weighed e-MRI has increased diagnostic performance with a sensitivity of 83%. Yuen et al 27 exhibited a sensitivity and specificity of 82.1 and 100%, with a PCa detection rate of 29.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Comet-Battle et al 25 had similar results, with a sensitivity of 80% and specificity of 76% using sextant PB for correlation. Beyersdorff et al 26 exhibited that T2-weighed e-MRI has increased diagnostic performance with a sensitivity of 83%. Yuen et al 27 exhibited a sensitivity and specificity of 82.1 and 100%, with a PCa detection rate of 29.2%.…”
Section: Discussionmentioning
confidence: 99%
“…DCE-MRI and MRS were mentioned as techniques that could be useful for staging, therapy planning and for detecting recurrent disease. The 2006 RCR guidance is currently being updated under the Cancer Staging Proforma Reporting Project (CASPAR), 44 which is a pilot programme to test the design and utility of proforma-based reporting for a number of cancers. The CASPAR PC imaging proforma provides guidance on the use of T2-MRI, DW-MRI and DCE-MRI (Dr Gina Brown, Project Lead, 27 February 2012, personal communication).…”
Section: Current Service Costmentioning
confidence: 99%
“…With a sensitivity of 53.3%, a specificity of 60%, and an accuracy rate of 55%, TRUS is limited in the detection of tumor recurrence during the follow-up of prostate cancer patients who have undergone EBRT. Beyersdorff et al have compared digital examination, TRUS, and MRI, and they have found that the sensitivity of MRI (83%) in the detection of prostate cancer is higher than that of digital examination (67%) and TRUS (57%) (5 than TRUS in the detection of prostate cancer but is less specific than TRUS (6). Although these studies were not conducted with patients who were not treated with EBRT, several studies have also reported and shown that TRUS is unreliable for the detection of cancer recurrence after EBRT (7-9).…”
Section: Discussionmentioning
confidence: 99%